Pemeliharaan Benih Ikan Jelawat (Leptobarbus hoeveni Blkr) dengan Padat Tebar Yang Berbeda Pada Sistem Resirkulasi dan Akuaponik - Rusliadi Rusliadi; Iskandar Putra; Syafriyandi Syafriyandi (Fakultas Perikanan dan Kelautan, Universitas Riau, 2015)
This research was conducted for 30 day from 28 September to 28 Oktober 2014, at Laboratory Aquaculture of Technology Universitas of Riau. The aimed of the study was to determine the effects of stocking density of Jelawat fish (Leptobarbus hoeveni Blkr) on the recirculation aquaponic system. The method this research was experiment with three treatments and three replications. The treatments were density of 20, 30 and 40 fish per 100 L waters, and 40 kemangi (Ocimum sanctum L) of each treatment. The best result of this research was on treatment 30 fish/ 100 L with absolute growht weight 3.03 g, the length of the absolute 1.67 cm, and daily growth rate 1.99% and the survival rate 90%. The best water quality parameters recorded during in the research period was achieved by. 30 fish/100 L of ammonia (NH3) 0.6602-0.2942 mg/L, nitrite (NO2) 0.1104-0.0893 mg/L, nitrate (NO3) 0.1598-0.0972 mg/L, temperatur 27-30oC, pH 5.5-6.0 dissolved oxygen (DO) 4.41-5.48 mg/L, and (CO2) 7.07-10.73 mg/L respectively